Cultural and ecological significance of Odonata (Insecta) to the T'boli of Lake Sebu, Mindanao, Philippines - Rizalyn Cudera; Brando Razon; Kenette Jean Millondaga (Society for Indonesian Biodiversity, 2020)
Abstract. Cudera RB, Razon BC, Millondaga KJI. 2020. Cultural and ecological significance of Odonata (Insecta) to the T'boli of Lake Sebu, Mindanao, Philippines. Biodiversitas 21: 2536-2554. Lake Sebu in Mindanao, Philippines, covered by the Allah Valley Protected Landscape, is home to the T'boli ethnolinguistic group. This study focuses on the cultural and ecological significance of the Odonata (insect order of dragonflies and damselflies) to the T'boli people who are known to have a close connection to their natural environment. According to the T'boli who participated in-depth interviews and focus group discussions, the Odonate larvae of Family Libellulidae and Aeshnidae known as Kmimi and Ogong El respectively are handpicked by the village members as a food source shared in the community when resources are scarce. The Odonata larvae are also used to cure illnesses and are locally believed to be important components for a love potion. In agriculture, T'boli farmers utilize the adult form of Odonata known as Klowong as natural biocontrol agents. Moreover, the Odonata larvae are prominent images in T'boli oral literature, specifically folklore and lullabies, teaching the children the importance of maintaining a harmonious relationship with nature. The results show that the presence of endemic species of Odonata indicates a healthy freshwater environment in the area; thus, studies on the sustainable use and conservation measures of the Odonata should be conducted.